Germination and regeneration mechanisms in Mediterranean degenerate forests - Bacilieri, R; Bouchet, M A; Bran, D; Grandjanny, M; Maistre, M; Perret, P; Romane, F (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.
Keywords: Castanea sativa; Pinus pinaster; Quercus ilex; Quercus pubescens